2011
DOI: 10.1089/scd.2010.0219
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Tracking of Pluripotent Human Embryonic Stem Cells with Dual Fluorescence Resonance Energy Transfer Molecular Beacons

Abstract: Pluripotent human embryonic stem cells (hESCs) provide an unprecedented opportunity for the study of human tissue development, and the development of cell-based therapies for human disease. To realize these potential advances, however, methods for monitoring expression of intracellular proteins in live hESCs without altering cellular properties are needed. Molecular beacons are single-stranded oligonucleotides that have been employed to assay gene expression. To test their potential for high-throughput isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…The reagent (4-10 mg) was incubated with 120 mM CaCl 2 and HEPES buffer containing NaCl, NaHPO 4 , and HEPES, pH 7.1, for 10 minutes on ice. The mixture was immediately added to the surface of the cultured cells, swirled gently, and returned to the incubator at 37°C with 5% CO 2 until needed.…”
Section: Calcium Phosphate Precipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The reagent (4-10 mg) was incubated with 120 mM CaCl 2 and HEPES buffer containing NaCl, NaHPO 4 , and HEPES, pH 7.1, for 10 minutes on ice. The mixture was immediately added to the surface of the cultured cells, swirled gently, and returned to the incubator at 37°C with 5% CO 2 until needed.…”
Section: Calcium Phosphate Precipitationmentioning
confidence: 99%
“…Although RNA beacons can be developed to detect genes associated with pluripotency (e.g., Oct4, nanog, Sox2) [1,4], many stem cell applications create induced pluripotent stem cells and induce them to differentiate toward specific lineages [5] by introducing specific genes (often transcription factors). Current selection methods require a distinctive surface marker that can detect target cells using antibodies or require introduction of a reporter gene such as green fluorescent protein (GFP).…”
Section: Introductionmentioning
confidence: 99%
“…adapted dual-fluorescence resonance energy transfer "molecular beacon" technology for transient, real-time detection of gene expression during hESC differentiation (62). Molecular beacons are single-stranded oligonucleotide probes that have been employed to assay gene expression in vitro, as in realtime PCR, and in vivo using microscopy.…”
Section: Reviewmentioning
confidence: 99%
“…Molecular beacons are single-stranded oligonucleotide probes that have been employed to assay gene expression in vitro, as in realtime PCR, and in vivo using microscopy. These investigators showed that appropriately designed, dual-fluorescence resonance energy transfer molecular beacon pairs can identify the expression of specific mRNAs and facilitate the collection of specific hESC populations by fluorescence-activated cell sorting, while leaving the hESC genome intact (62).…”
Section: Reviewmentioning
confidence: 99%
“…Dual FRET molecular beacons have been used to detect K-Ras, surviving and oct4 mRNAs in HDF, Miapaca-2, and H1 cells, respectively [66,72]. Interestingly, k-Ras mRNAs seemed to localize with a filamentous pattern in HDF cell whereas survivin mRNAs seemed to localize in a non-symmetrical pattern within Miapaca-2 cells, often to one side of the nucleus of the cell.…”
Section: Molecular Beaconsmentioning
confidence: 99%